2012
DOI: 10.1523/jneurosci.2045-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Teneurin-4 Is a Novel Regulator of Oligodendrocyte Differentiation and Myelination of Small-Diameter Axons in the CNS

Abstract: Myelination is essential for proper functioning of the central nervous system (CNS). In this study, we have identified a mouse mutation, designated furue, which causes tremors and hypomyelination in the CNS, particularly in the spinal cord, but not in the sciatic nerve of the peripheral nervous system (PNS). In the spinal cord of the furue mice, myelination of small diameter axons was dramatically reduced and differentiation of oligodendrocytes, the myelin-forming cells in the CNS, was inhibited. We subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 29 publications
3
84
0
2
Order By: Relevance
“…For analyses of the Ten‐4 function in satellite cells, we used the furue ( fur ) mutant mouse line whose Ten‐4 expression is absent because of a transgene insertion in the Ten‐4 gene ( Odz4 / Tenm4 ) 23. The mutant fur / fur mice are hereafter referred to as Ten‐4−/− mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For analyses of the Ten‐4 function in satellite cells, we used the furue ( fur ) mutant mouse line whose Ten‐4 expression is absent because of a transgene insertion in the Ten‐4 gene ( Odz4 / Tenm4 ) 23. The mutant fur / fur mice are hereafter referred to as Ten‐4−/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion to the basement membrane and the myofiber plasma membrane is crucial for the quiescence of satellite cells in their niche 28. We have previously reported that Ten‐4 regulates the activation of focal adhesion kinase, a critical downstream molecule of integrins and dystroglycan, in neural and glial cells 23, 28, 29. Therefore, Ten‐4 may play a key role in satellite cells at the quiescent state together with these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, deletions of teneurin-3 result in impairments of axonal guidance in the visual system and cause mistargeting of axons from the retina to the geniculate nucleus and the superior colliculus (18,19). In contrast, deletions of teneurin-4 impair oligodendrocyte differentiation and myelination (20). In Drosophila, conversely, teneurin mutations produce a defect in motor axon guidance, although overexpression studies suggested a role for teneurins in target selection during synaptogenesis (8,9).…”
mentioning
confidence: 99%
“…Teneurin proteinlerinin hücre haberleşmesinde ve oligodentrosit diferensiasyonu, santral sinir sistemindeki sinirlerin miyelinizasyonu gibi kritik roller oynadığına dair çalışmalar literatür çalışmaları yayınlanmaya başlamıştır (22).…”
Section: İkiz çAlışmalarıunclassified